Halal product price indicator portal: promoting Malaysia’s local Halal SMEs - Machfud, Alfi Khairiansyah; Khatib, Jawdat; Haji-Ahmed, Ahmed Abdulaziz; Ahmad Dahlan, Abdul Rahman (Springer New York LLC, 2011)
Local halal small and medium enterprises (SMEs) play an important role in Malaysia’s future economy. Currently the popularity of their products is still low compare to those of the large and multinational companies. A Halal Product Price Indicator Portal is proposed to help promote and improve the condition of the SMEs. The portal involves Malaysia Department of Islamic Development (JAKIM) and local Halal SMEs in Malaysia. The main feature of the portal is Halal products price information and comparison functionality. It is believed that the establishment of the portal will encourage people to view it, and in time, will help promote local Halal SMEs and made their products more accessible to customers and eventually contribute to national development.